Respuesta :
ANSWER
[tex]x=\sqrt{3}-1[/tex] or [tex]x=-\sqrt{3}-1[/tex]
EXPLANATION
To complete the square for [tex]x^2+2x-2=0[/tex].
We rewrite the equation to get
[tex]x^2+2x=2[/tex].
We now add [tex](1)^2[/tex] to both sides to get
[tex]x^2+2x+1^2=2+1^2[/tex].
The expression on the Left Hand Side of the equation is a perfect square.
So our equation becomes
[tex](x+1)^2=2+1[/tex]
This gives us,
[tex](x+1)^2=3[/tex]
We take square root of both sides to obtain,
[tex]x+1=\pm \sqrt{3}[/tex]
[tex]x=-1\pm \sqrt{3}[/tex]
We split the [tex]\pm[/tex] to obtain,
[tex]x=\sqrt{3}-1[/tex]
or
[tex]x=-\sqrt{3}-1[/tex]
Answer:
x = √3 - 1 and x = -√3 - 1
Step-by-step explanation:
x^2 +2x - 2 = 0
To solve this equation, keep the variables on one side and constants on the other
x^2 + 2x = 2
Now to complete the square, divide the coefficient of x by 2:
2x ---> coefficient of x is 2
so 2/2 = 1
Now add the square of 1 to both the sides of the equation:
x^2 + 2x + (1)^2 = 2 + (1)^2
which makes it
(x + 1)^2 = 3
To solve it, take square root of both sides which gives
x = √3 - 1 and x = -√3 - 1